Konsep Zuhud Syekh Nawawi Al-Bantani dan Relevansinya dengan Pembentukan Moral - Satria Satria; Bambang Qomaruzzaman (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The purpose of the study is to analyze the zuhud Syekh Nawawi al-Bantani concept and its relevance to moral formation. The study uses a qualitative approach by positioning the researcher as a core instrument that then combined with the character's biographical approach. Then the littering study was used to collect data by excavating various relevant sources. In the study, it found that the concept of zuhud Syekh Nawawi al-bantani has almost in common with other sufi figures, the concept of zuhud Syekh Nawawi al-bantani also teaches people to be not passive but active in various aspects of worldhood only serves to bring sense and logic to the afterlife. Then, the concept of zuhud Syekh Nawawi al-bantani also relates to the process of moral formation in society, as well as the zuhud Syekh Nawawi al-bantani's relevant is consumed by various societies, as well as its practice of changing conditions or times.